The Effect of Concrete Compressive Strength on Mixture and Curing Using River Water - Haz, Muhamad Hafda; Prabowo, Yudi Setio (Syntax Literate, 2025)
The primary concern addressed in this study is the impact of river water quality used in concrete mixing and curing on the compressive strength of concrete, considering that river water contains minerals and chemical ions that may inhibit cement hydration. The objective is to analyze the effects of varying water-cement ratios and curing durations using river water on concrete compressive strength and to provide technical recommendations applicable to construction practices in areas with limited clean water resources. The method involved laboratory experiments preparing 15x15x15 cm concrete cubes immersed in river water for 3 and 7 days, followed by compressive strength testing with a compression machine. The results showed that compressive strength increases with longer curing due to ongoing hydration, yet concrete cured with river water exhibited lower strength compared to that cured with clean water, attributed to minerals and chloride and sulfate ions interfering with hydration product formation. The implications highlight the importance of water quality testing and controlling the water-cement ratio to optimize concrete strength in projects using river water for curing, as well as the need for specific technical guidelines to ensure the safety and durability of concrete structures in water-limited environments.